2021
DOI: 10.3233/jad-201025
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Amyloid Aggregation in the Brain: V. Are Alzheimer’s and Other Amyloid Diseases Initiated in the Lower Brain and Brainstem by Cerebrospinal Fluid Flow Stresses?

Abstract: Amyloid-β (Aβ) and tau oligomers have been identified as neurotoxic agents responsible for causing Alzheimer’s disease (AD). Clinical trials using Aβ and tau as targets have failed, giving rise to calls for new research approaches to combat AD. This paper provides such an approach. Most basic AD research has involved quiescent Aβ and tau solutions. However, studies involving laminar and extensional flow of proteins have demonstrated that mechanical agitation of proteins induces or accelerates protein aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…[18] and expanded [5] based on the report of chaotic motions of the CSF within certain regions of the brain, especially in basal regions [3]. In this paper, this new approach is expanded to include anatomical correlations between A␤/tau pathology and regions shear in perivascular flow paths in the brain vascular system.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
See 4 more Smart Citations
“…[18] and expanded [5] based on the report of chaotic motions of the CSF within certain regions of the brain, especially in basal regions [3]. In this paper, this new approach is expanded to include anatomical correlations between A␤/tau pathology and regions shear in perivascular flow paths in the brain vascular system.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Whether or not there are chemical reactions relating to these conformational perturbations will depend on their energy as well as opportunities for reactions of the excited tau or A␤ molecules with their surroundings such as other stretched molecules or nearby membrane surfaces [71]. Figure 3 Putting all these facts together, it has been suggested that flow-induced stresses within the lower brain and cistern regions may be responsible for the initiation of A␤ and tau aggregation-and subsequent AD disease [5]. In this light, the decadal timing of this disease is of great interest.…”
Section: Tau and Tau Oligomersmentioning
confidence: 99%
See 3 more Smart Citations